Qualitative Study on The Implementation of Pharmacy Management Information Systems in Hospitals - Amelia Sari (Indonesian Journal Publisher, 2026)
This study aims to explore the implementation of the Pharmacy Management Information System (SIMF) in hospitals, focusing on supporting factors, obstacles, and benefits obtained in operational practices and pharmacy management. The method used is qualitative research with a descriptive approach through a literature study, where data is collected from scientific literature, official reports, and relevant documents related to SIMF. Data analysis was conducted inductively through theme identification, data reduction, concept categorization, and systematic interpretation of findings to obtain a comprehensive understanding of the phenomenon under study. The results showed that SIMF improved operational efficiency, reduced medication errors, and improved drug stock management, with the support of automation technology, AI, and integrated systems. Human and organizational factors, such as staff training, multidisciplinary team involvement, and management support, proved to be key drivers, while limitations in training, system integration, and staff resistance were obstacles that needed to be overcome. These findings provide practical insights for hospital management in optimizing PIMIS implementation and enrich the academic literature on information technology adoption in pharmacy. In conclusion, this study makes a significant contribution to the understanding of factors influencing the successful implementation of PIMIS, offers adaptation strategies, and supports the improvement of service quality and patient safety in hospitals.